2001
DOI: 10.1088/0957-4484/12/4/308
|View full text |Cite
|
Sign up to set email alerts
|

MBE growth of high-quality GaAsN bulk layers

Abstract: Abstract. In the present work we have carefully optimized the operation of plasma source and the growth parameters of GaAsN layers. We have demonstrated the possibility of incorporation about 1.5% of N into GaAs without decreasing the photoluminescence intensity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…The incorporation of N in GaAs has been found to be temperature independent in a wide range of temperatures from 400°C to 480°C [19] or even higher temperatures [20,21]. However, for temperatures higher than that, N incorporation is strongly reduced.…”
Section: Resultsmentioning
confidence: 99%
“…The incorporation of N in GaAs has been found to be temperature independent in a wide range of temperatures from 400°C to 480°C [19] or even higher temperatures [20,21]. However, for temperatures higher than that, N incorporation is strongly reduced.…”
Section: Resultsmentioning
confidence: 99%
“…After heat treatment removal of native oxide from the GaAs (0 0 1) substrate, a GaAs buffer of 200 nm was grown at about 580 1C, and then 100 nm GaN x As 1Àx films were grown at 460 1C. The growth rate was 0.57 ML/s for GaAs, which is much lower than the conventional growth rates (higher than 1 ML/s) [5]. However, a 2D growth mode was realized during the whole growth stage as indicated by the reflective highenergy electron diffraction (RHEED), and the surface was very smooth (typical root-square-mean smoothness of 0.18 nm) as checked by atomic force microscope (AFM).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it is concluded that Indium stimulates phase separation regardless of strain compensation, probably because the presence of indium enhances migration of nitrogen atoms. 24 Figure 4(a) shows the dependence of the integrated PL intensity of GaAs and GaAsN samples grown at different temperatures on PL peak position as well as the corresponding PL spectra. One can see that the integrated PL intensity depends on growth temperature and is independent with the presence of nitrogen in the layers.…”
Section: Effect Of Growth Temperature and Growth Ratementioning
confidence: 99%